Direct Observation of Stacking Fault Nucleation from Deflected Threading Dislocations with Burgers Vector c+a in PVT Grown 4H-SiC. Issue 1693 (10th June 2014) - Wu, Fangzhen; Wang, Huanhuan; Raghothamachar, Balaji; Dudley, Michael; Mueller, Stephan G.; Chung, Gil; Sanchez, Edward K.; Hansen, Darren; Loboda, Mark J.
ABSTRACT: In our previous studies [1-3], four kinds of stacking faults in 4H-SiC bulk crystal have been distinguished based on their contrast behavior differences in synchrotron white beam x-ray topography images. These faults are Shockley faults, Frank faults, Shockley plus c/2 Frank faults, and Shockley plus c/4 Frank faults. Our proposed formation mechanisms for these stacking faults involve the overgrowth of the surface outcrop associated with threading screw dislocations (TSDs) or threading mixed dislocations (TMDs) with Burgers vector of c+a by macrosteps and the consequent deflection of TSDs or TMDs onto the basal plane. Previous synchrotron x-ray topography observations were made in offcut basal wafers using transmission geometry. In this paper, further evidence is reported to confirm the proposed stacking fault formation mechanism. Observations are made in axially cut slices with surface plane {11-20}. Several kinds of stacking faults are recognized and their contrast behavior agrees with the four kinds previously reported. Direct observation is obtained of a Shockley plus c/4 Frank stacking fault nucleating from a TMD deflected onto the basal plane. The contrast from stacking faults on the basal plane in the axial slices is enhanced by recording images after rotating the crystal about the active -1010 reflection vector enabling a broader projection of the basal plane.